Effect of thermomechanical processing on evolution of various phases in Ti-Nb alloys - Banumathy S.; Prasad K.S.; Mandal R.K.; Singh A.K. (My University, 2025)
This paper deals with the effect of thermomechanical processing on microstructural evolution of three alloys, viz. Ti-8Nb, Ti-12Nb and Ti-16Nb. The alloys were hot rolled at 800°C and then subjected to various heat treatments. Samples from hot-rolled alloys were given solution-treatment in β and α + β phase fields, respectively followed by water quenching and furnace cooling. The solution-treated alloys were subsequently aged at different temperatures for 24 h. Phases evolved after various heat treatments were studied using X-ray diffractometer, optical, scanning and transmission electron microscopes. The alloy Ti-8Nb exhibits α and β phases while the alloys Ti-12Nb and Ti-16Nb show the presence of α″, β and ω phases in the as-cast and hot-rolled conditions. The β solution treated and water quenched specimen of the alloy Ti-8Nb displays α″ phase while the alloys Ti-12Nb and Ti-16Nb exhibit α″, β and ω phases. The alloy Ti-8Nb shows the presence of α , β and ω phases while those of Ti-12Nb and Ti-16Nb display the presence of α , α″, β and ω in α + β solution treated and water quenched condition. The observation of ω phase in solution treated condition depends on the cooling rate and the Nb content while in the aged specimens, it is governed by aging temperature as well as the Nb content.